Análise in vitro da atividade antioxidante do suco e extrato de maçã em células RINm5f submetidas a diferentes condições de estresse oxidativo - Anzuategui, Lorene Simioni Yassin (2009)
The phenolic compounds, found in vegetables and fruits, may have a high antioxidant activity. Apple, world’s second largest produced fruit, is classified as having one of the high antioxidant potential due to its content and profile of phenolic compounds. The aim of this research was to evaluate the antioxidant activity of apple and check its effect on cells secreting insulin (RINm5f) subjected to oxidative stress induced by high concentration of glucose (GA) and H2O2. Once prepared juices and extracts of whole fruit, flesh and epicarp of Gala and Fuji cultivars, the following parameters were analyzed: total non-reducing sugars (AT), total phenols content (FT), antioxidant activity (AA) before and after centrifugation and filtration. Cytotoxicity, cell viability (VC) on oxidative stress and production of intracellular superoxide analysis were performed in biological tests. Several dilutions (1:10, 1:50, 1:100, 1:250) and quantities of extracts (5, 10, 50,100 and 250 mg/mL) of apple juice were tested to evaluate cytotoxicity. To evaluate biological effects, juice dilutions of 1:50, 1:100 and 1:250 were used for Gala and Fuji apple. Epicarp extracts concentration of 10, 50 and 100 mg/mL were used for Gala apple and 10 mg/mL for Fuji apple. In the whole fruit and fruit flesh, AT content ranged from 41.69 to 50.80 g/100g and epicarp’s was about 10 times less. Gala and Fuji juice AT content was, respectively, 12.94 g and 10.33 g/100g. Big loss of FT and the AA was observed after centrifugation and especially after filtration. Highest amount of FT was found in epicarp extract of Fuji apple before filtration. After filtration the highest concentration of FT was in extracts of Gala apple. Even presenting less FT than Gala apple after filtering, the epicarp extract of Fuji apple kept higher AA. Gala apple juice presented more FT and AA before and after filtration than Fuji apple juice. During cytotoxicity test, only Fuji apple epicarp extract at concentrations above 10 g/mL was cytotoxic. Under GA induced stress, Gala apple epicarp extract (10 mg/mL), all tested dilutions of Gala apple juice and the Fuji apple juice (1:250), increased the VC. Fuji apple juice showed cytotoxic effect on dilution 1:10. Gala apple apicarp extract (10, 50 and 100 g/mL) Fuji apple juice (1:250), reduced production of intracellular superoxide. Gala and Fuji apple juice (1:50 and 1:100) had cytoprotectant effect under H2O2 induced stress, increasing VC when compared to H2O2 group. However, none of the juices tested was able to significantly reverse the damage caused by H2O2 when cell morphology was evaluated. Significant increase of 50% on average in the secretion of insulin was observed in Gala apple juice (1:100 and 1:250) and Fuji apple juice (1:50). It could be concluded that according to oxidative stress type and extract of epicarp and juice of Gala and Fuji apples concentration, oxidative stress on cells RINm5f may be reduced.